A student’s perspective: utilizing the lived experience of healthcare leaders as a professional development tool - Dewsnap, Michael A.; Konatham, Sunitha E. (Frontiers in Medicine, 2025)
Recent events like the COVID-19 pandemic or operational innovations such as the increased use of advanced providers have compelled physicians to take on additional roles like public health spokesperson or team leader. Lectures and workshops are common educational tools utilized to address these changing roles but require significant time, resources, and are often overshadowed by preference for personal experience. The purpose of this commentary is to suggest that the lived experience of healthcare leaders, as expressed through qualitative research-based interviews, offer an engaging educational tool for professional development of the interviewee and the interviewer, especially when a student is the interviewer. Through a student’s perspective, and building off a class project, three healthcare leaders were interviewed, and the responses analyzed. Common themes such as approachability, perspective taking, vision establishment, and team empowerment were identified. The student’s, and the supervising faculty co-author’s, reflections illustrate the impact of using this qualitative research approach to broaden their insights into the complexities associated with being a leader in a healthcare system that incorporates clinical care and educational requirements. However, scaling this tool to a medical school class, or student body, would require altering the method such as group interviews.